Beyond the Conversation: The Pervasive Danger of Slurs - Alba Moreno (Institute of Philosophy of the Slovak Academy of Sciences, 2021)
Although slurs are conventionally defined as derogatory words, it has been widely noted that not all of their occurrences are derogatory. This may lead us to think that there are “innocent” occurrences of slurs, i.e., occurrences of slurs that are not harmful in any sense. The aim of this paper is to challenge this assumption. Our thesis is that slurs are always potentially harmful, even if some of their occurrences are nonderogatory. Our argument is the following. Derogatory occurrences of slurs are not characterized by their sharing any specific linguistic form; instead, they are those that take place in what we call uncontrolled contexts, that is, contexts in which we do not have enough knowledge of our audience to predict what the uptake of the utterance will be. Slurs uttered in controlled contexts, by contrast, may lack derogatory character. However, although the kind of context at which the utterance of a slur takes place can make it nonderogatory, it cannot completely deprive it of its harmful potential. Utterances of slurs in controlled contexts still contribute to normalizing their utterances in uncontrolled contexts, which makes nonderogatory occurrences of slurs potentially harmful too.